2014
DOI: 10.5935/0101-2800.20140064
|View full text |Cite
|
Sign up to set email alerts
|

Computerized Tomography Contrast Induced Nephropathy (CIN) among adult inpatients

Abstract: Of a total of 410 patients, 35 (8.5%) developed CIN. There was a positive correlation between CIN and the presence of diabetes mellitus (OR = 2.15; 95%CI 1.35-4.06; p = 0.02), heart failure (OR = 2.23; 95%CI 1.18-8.8; p = 0.022), and renal failure (OR = 3.36; 95%CI 1.57- 7.17; p = 0.002) CONCLUSION: Incidence of CIN varies according to the population. Diabetes mellitus, heart failure and renal failure were independent risk factors for the development of CT-associated CIN. Further studies are needed to better u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
0
6
0
5
Order By: Relevance
“…In previous studies, Selistre et al [20] observed no association between fluid administration and CIN occurrence. Diogo et al [35] reported a low rate of prehydration therapy in Brazil.…”
Section: Survived N=48mentioning
confidence: 99%
“…In previous studies, Selistre et al [20] observed no association between fluid administration and CIN occurrence. Diogo et al [35] reported a low rate of prehydration therapy in Brazil.…”
Section: Survived N=48mentioning
confidence: 99%
“…Только 0,15-12% пациентов, у которых развивается КИН, требуют медицинского вмешательства [74]. У пациентов с высоким риском важно использовать минимальную дозу низко-или изоосмолярных КВ, необходимых для повышения качества диагностики, или применять альтернативные методы визуализации [22]. В течение многих лет в литературе, посвященной КИН, обсуждалось предположение, что большая часть острых почечных повреждений, которые по времени связаны с введением йодсодержащих КВ, должны рассматриваться как связанные собственно с самим КВ, а не с другими ранее существующими нефротоксичными факторам риска [75] [77] -час тота выявления пациентов, отвечающих критериям КИН после бесконтрастной КТ, похожа на ту, что наблюдали у пациентов после КТ с контрастным усилением.…”
Section: Discussionunclassified
“…Так, Diogo L.P. и соавт. [22] рекомендуют в среднем вводить 139,1 ± 31,2 мл КВ, а для корректировки объема они учитывают площадь поверхности тела (тогда объем КВ будет равен 81,0 ± 2,1 мл/м 2 ) [22].…”
Section: результатыunclassified
See 2 more Smart Citations